Penanganan Kekerasan dalam Implementasi Kebijakan Kota Layak Anak di Surabaya - Titis Dewi Cahyani; Suci Megawati; Tjitjik Rahayu; Ahmad Nizar Hilmi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Cases of violence against children in the City of Surabaya continue to occur despite the city's achievement of the Main Category Child-Friendly City (Kota Layak Anak/KLA) designation and its international recognition by UNICEF. This condition indicates that the implementation of the Child-Friendly City policy, particularly in addressing violence against children, still requires greater attention and strengthening. This study aims to describe the handling of child violence within the implementation of the Child-Friendly City policy in Surabaya. The research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation. The analysis of policy implementation was based on George C. Edward III’s policy implementation framework, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate that the policy has been implemented relatively well through cross-sectoral coordination, public outreach and socialization programs, the utilization of the SIAP PPAK information system, and the support of standard operating procedures (SOPs) and inter-agency collaboration. However, several challenges remain, including a shortage of psychologists and counselors, the uneven distribution of PUSPAGA facilitators, and the suboptimal use of digital media. Therefore, strengthening human resources, expanding service coverage, and optimizing information systems are necessary to improve the effectiveness of efforts to address violence against children in the City of Surabaya.